Життєвий та науковий шлях академіка В.П. Кухаря - Boyko, Oleksandr; Patrylak, Lyubov (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2022)
Academician V. P. Kukhar: scientist and personality